2021
DOI: 10.1186/s13018-021-02227-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for rapid progressive neurological deterioration in patients with cervical spondylotic myelopathy

Abstract: Background The rapid progressive cervical spondylotic myelopathy (rp-CSM) which had a course of CSM less than 1 month and suffered rapidly progressive neurological deterioration had few reports. Therefore, it is important for us to recognize the pathophysiology of CSM especially the rp-CSM. The study aimed to investigate the risk factors for rapidly progressive (rp) neurological deterioration in patients with cervical spondylotic myelopathy (CSM). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Our investigation revealed that ISI of the spinal cord on T2WI and high degree disc degeneration in the cranial adjacent levels emerged as idependent risk factors affecting the recovery of patients' neurological functions. Remarkably, 90% of patients in the "poor" group exhibited ISI of the spinal cord on T2WI in our study.The ISI of the spinal cord on T2WI mirrors the underlying pathology of spinal cord injury, encompassing edema, gliosis, demyelination, and spinal cord chondromalacia [30] .At the same time, an ISI of the spinal cord on T2WI in might indicate secondary spinal cord edema due to acute spinal cord ischemia, posing as a idependent risk factors for rapid progressive neurological deterioration in patients a icted with cervical spondylosis [16] .Uchida et al [31] elucidated that ISI of the spinal cord on preoperative T2WI signi es a manifestation of severe, potentially irreversible chronic spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…Our investigation revealed that ISI of the spinal cord on T2WI and high degree disc degeneration in the cranial adjacent levels emerged as idependent risk factors affecting the recovery of patients' neurological functions. Remarkably, 90% of patients in the "poor" group exhibited ISI of the spinal cord on T2WI in our study.The ISI of the spinal cord on T2WI mirrors the underlying pathology of spinal cord injury, encompassing edema, gliosis, demyelination, and spinal cord chondromalacia [30] .At the same time, an ISI of the spinal cord on T2WI in might indicate secondary spinal cord edema due to acute spinal cord ischemia, posing as a idependent risk factors for rapid progressive neurological deterioration in patients a icted with cervical spondylosis [16] .Uchida et al [31] elucidated that ISI of the spinal cord on preoperative T2WI signi es a manifestation of severe, potentially irreversible chronic spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis and treatment are still important to preserve as much function as possible since our findings, as well as findings from previous studies have shown that duration of symptoms has some effect as a predictor of surgical outcome. 7,23 Longer duration of symptoms does not, however, always mean that the disease is severe, since some patients live with mild symptoms for years without progression, while others progress quickly to a very severe degree of the disease, 24,25 Furthermore, a long duration of mild symptoms may not have been prioritized for surgical treatment, thus leading to a longer duration of symptoms before treatment. Type of surgery was not a predictor of outcome in accordance with recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to conduct physical examinations for patients with suspected CSM. However, the symptoms of CSM are almost always insidious ( 3 ), which makes the diagnosis of CSM very challenging ( 4 ). Currently, imaging is still an important approach for evaluating suspected CSM.…”
Section: Introductionmentioning
confidence: 99%